Multi-island Genetic Algorithm Opetimization of Suspension System - Jing-Jun Zhang; Li-Wei Xu; Rui-Zhen Gao (Institute of Advanced Engineering and Science, 2012)
The suspension and the car's operating stability are closely linked. Through the optimization of the suspension, it can improve the operating stability of vehicle, which is very meaningful to enhance the performance of modern cars. With the development of science and technology, the traditional optimization methods often appear insufficient when it deals with the multi-objective optimization problem of the automotive suspension. As a kind of improved genetic algorithm, the multi-island genetic algorithm can handle the multi-objective problem very well. In order to improve the vehicle handling stability, in this paper, the multi-island genetic algorithm is used to optimize the suspension parameters, combined with the iSight-FD and the Adams/car. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1563